Pendampingan Diversifikasi Produk Berbahan Baku Lele Asap Menjadi Lele Asap Masak Mangut Daun Kemangi Di Desa Sampora - Indriati, Kumala; Widjayanti, Linda (Jurnal Pengabdian Masyarakat Charitas, 2022)
Catfish is a type of freshwater fish that contains protein, omega-3 and omega-6 acids in its body. Catfish also contains vitamins B1, B2, phosphorus, calcium, iron, sodium, and niacin. To prevent excessive levels of calories, fat and cholesterol in the body, it is necessary to avoid processing catfish by frying. Instead, it is necessary to try how to process catfish by smoking. After providing assistance in making smoked catfish for the Sampora Village Community, the Community Service Team of the Faculty of Engineering Atma Jaya Catholic University of Indonesia introduced various dishes made from smoked catfish, one of which was smoked catfish mangut cooked with basil leaves to PKK women in Sampora village. The benefit of this community service activity is to equip the community to open a processed food business made from smoked catfish which will later become the typical food of the Sampora village. This community service activity also provides practical assistance in the form of marketing through social media.